Students’ Writing Anxiety and Its Correlation with Their Writing Performance - Rasuan, Zulfikri; Wati, Lindra (EEdJ: English Education Journal, 2021)
The objectives of this study were to find out: (1) the dominant aspect in writing anxiety, (2) the correlation between students’ writing anxiety and their writing performance, (3) the differences between male and female students in students’ writing anxiety of the twelfth grade students in Pangkalpinang, Bangka Belitung. The sample of this study was 80 students The instruments used were writing anxiety questionnaire and a writing test. The results showed that, cognitive was the most dominant aspect. There was a fair significant correlation between students’ writing anxiety and writing performance. T-score was -0,430 and T-table was 0,283. The result showed that, there was a negative and strong enough correlation between the students’ writing anxiety and their writing perfomance. English learning anxiety gave positive influences to the students’ writing performance, not necessarily bad result to writing but drove the students to get motivation to be better from others. In addition, the result of writing anxiety showed that the mean score of male students was 100,27 and the females got 102,60. So, there was a significant difference between male and female students. Thus, the teachers are suggested to increase students’ self-confidence so that students’ writing results are maximized.